ANALISIS FAKTOR YANG MEMPENGARUHI MINAT WISATAWAN DOMESTIK BERKUNJUNG KE BALI - Bagus Putu Widanta, AA.; Ketut Ayuningsasi, AA. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 2 (2021): Jurnal IPTA (December 2021), 2021)
Domestic tourists contribute no less than foreign tourists to Bali tourism. The number of domestic tourists visits far exceeds than the number of foreign tourists, which is has a significant impact on Bali's economic growth. The prospect of domestic tourists is very large, it is necessary to pay attention and analyze the factors that influence the interest of domestic tourist revisit to Bali. Factors that attract investment, people (tourists) and industry to an area, namely; image is the beliefs, ideas and expressions that a person has towards an area; attraction marketing/attraction of tourist destinations is an important reason for tourists, investors and capital to visit a place; infrastructure marketing is the availability of facilities and infrastructure that can attract people, investment and capital; and people marketing strategy to promote the area by marketing people, for example the attitude of the community: how much openness of the local community (regional) to elements (people, investment, industry, products) from other area; Price is a number of expenses spending during visit an area, including the price of accommodation, restaurants, transportation and performances in an area. Image, infrastructure marketing, attraction marketing, people marketing, have a positive and significant effect, except that price has a positive and insignificant effect on the interest of domestic tourist revisit to Bali. Identification of variables that influence the interest of domestic tourists to be a reference for decision making and policies for related parties to develop the direction of tourism policies on Bali in particularly and Indonesia in generally.